[Re(η6-arene)2]+ as a highly stable ferrocene-like scaffold for ligands and complexes. Issue 16 (3rd April 2020) - Hernández-Valdés, Daniel; Avignon, Frédéric; Müller, Peter; Meola, Giuseppe; Probst, Benjamin; Fox, Thomas; Spingler, Bernhard; Alberto, Roger
Abstract : Sandwich complexes [Re(η 6 -C6 H6 )2 ] + are versatile scaffolds for conjugating a variety of ligands, as in ferrocene. The high stability of a so-prepared Re/Co system under light irradiation is exemplified with photocatalysis for proton reduction. Abstract : Ferrocenes are versatile ligand scaffolds, complexes of which have found numerous applications in catalysis. Structurally similar but of higher redox stabilites are sandwich complexes of the [Re(η 6 -arene)2 ] + type. We report herein routes for conjugating potential ligands to a single or to both arenes in this scaffold. Since the arene rings can freely rotate, the [Re(η 6 -arene)2 ] + has a high degree of structural flexibility. Polypyridyl ligands were successfully introduced. The coordination of Co(ii ) to such a model tetrapyridyl-Re(i )-bis-benzene complex produced a bimetallic Re(i )–Co(ii ) complex. To show the stability of the resulting architecture, a selected complex was subjected to photocatalytic reactions. It showed good activity in proton reduction over a long time and did not decompose, corroborating its extraordinary stability even under light irradiation. Its activity compares well with the parent catalyst in turn over numbers and frequencies. The supply of electrons limits catalytic turnover frequency at concentrations below ∼10 μM. We also show that other ligands can be introduced along these strategies. The great diversity offered by [Re(η 6 -arene)2 ] + sandwich complexes from a synthetic point allows this concept to be extended to other catalytic processes, comparable to ferrocenes.